Chemical and photochemical functionality of the first molecular bismuth vanadium oxide - Tucher, Johannes; Nye, Leanne; Ivanovic-Burmazovic, Ivana; Notarnicola, Antonio; Streb, Carsten (Chemistry - A European Journal, 2012)
Anionic metal oxide clusters, so-called polyoxometalates, can be developed as molecular model compounds to mimic the chemical and photochemical reactivity of solid-state metal oxides on the molecular level. Inspired by the well-known visible-light photocatalyst BiVO , the first molecular bismuth vanadium oxide has been synthesized to investigate the chemical and photochemical similarities between the solid-state and molecular compounds. The cluster H [(Bi(dmso) ) V O ]aca. 4a DMSO was obtained from simple precursors in almost quantitative yield. Structural analysis showed that the cluster shell is based on the unusual all-vanadium μ-Keggin framework [μ-V O ] , which is stabilized by coordination of four Bi centers. The acidic character of the three cluster protons was demonstrated by titration studies. The cluster shows promising photocatalytic properties in visible-light photooxidation reactions and has high activity (turnover number >1200), high quantum yield (∥=7.6a %), and good recyclability, which make it a promising first example of a new class of heterometallic polyoxometalates. An all-vanadium μ-Keggin anion [μ-(VO )V O ] is surrounded by a tetrahedral arrangement of four Bi centers in polyoxometalate 1 , which is the first structurally characterized bismuth vanadium oxide cluster (central V blue, V green, Bi orange). The cluster is acidic and photoactive under visible-light irradiation, and shows high turnover numbers and good quantum yields in the photooxidation of model pollutant patent blue V (PBV). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.